(untitled) (Swiss Medical Weekly, 2018)
BACKGROUND AND OBJECTIVES Hospitalisation influences drug therapy in ambulatory care and this influence is generally negatively perceived. The few studies that have explored changes in benzodiazepine or sleep medication use as a function of hospitalisation failed to precisely determine the hospital’s role in initiating, continuing and discontinuing these drugs on a valid basis. The aim of the study was to ascertain the overall influence of hospitalisation on the prescription of benzodiazepines and Z-drugs in outpatient care with a special focus on the role of different hospital departments and drug classes. METHODS In a secondary data analysis, we used prescription data for 181 037 patients who visited 127 hospitals and compared the numbers of patients with prescriptions of benzodiazepines and Z-drugs 50 days before and 50 or 100 days after hospitalisation. RESULTS The proportion of patients who received benzodiazepines or Z-drugs increased from 3.1% before admission to 3.6% at 50 days after discharge and fell to the former level after an additional 50 days. A multivariable logistic regression showed that gender and department had an additional impact on these results. Of those patients without a prescription for a benzodiazepine or Z-drug before admission, 0.6% received a prescription in both time-windows after discharge. Of those patients who were prescribed a benzodiazepine, 38.0% received short-acting substances and 40.3% received long-acting substances before hospitalisation. After hospitalisation, these rates changed to favour short-acting substances (44.4% and 34.4%, respectively). CONCLUSIONS The hospital effect on initiating and increasing hypnotic or sedative drug use seems to be only moderate and temporary. A change in favour of short-acting substances is even welcome. In less than 1% of patients, the hospital initiated the continuous use of benzodiazepines and Z-drugs, which may put pressure on primary care physicians. However, the widespread use of these drugs in hospitals does not seem to be continued on a large scale in primary care.